{{ item.displayTitle }}

No history yet!

equalizer

rate_review

{{ r.avatar.letter }}

{{ u.avatar.letter }}

+

{{ item.displayTitle }}

{{ item.subject.displayTitle }}

{{ searchError }}

{{ courseTrack.displayTitle }} {{ statistics.percent }}% Sign in to view progress

{{ printedBook.courseTrack.name }} {{ printedBook.name }} {{ greeting }} {{userName}}

{{ 'ml-article-collection-banner-text' | message }}

{{ 'ml-article-collection-your-statistics' | message }}

{{ 'ml-article-collection-overall-progress' | message }}

{{ 'ml-article-collection-challenge' | message }} Coming Soon!

{{ 'ml-article-collection-randomly-challenge' | message }}

{{ 'ml-article-collection-community' | message }}

{{ 'ml-article-collection-follow-latest-updates' | message }}

The general form of a quadratic equation is
*quadratic formula,* which is derived by completing the square.

ax2+bx+c=0,

where a, b, and c are real numbers, and a≠0. There are many ways to solve such equations. One way is by using the To solve a quadratic equation written in standard form ax2+bx+c=0, the Quadratic Formula can be used.

In this formula, the discriminant b2−4ac determines the number of real solutions of the quadratic equation.

The Quadratic Formula can be derived by completing the square given the standard form of the quadratic equation ax2+bx+c=0. This method will be used to isolate the x-variable. To complete the square, there are five steps to follow. ### 1

It is easier to complete the square when the quadratic expression is written in the form x2+bx+c. Therefore, the coefficient a should be factored out.
Since the equation is quadratic, the coefficient a is not equal to 0. Therefore, both sides of the equation can be divided by a.
### 2

The next step is to rewrite the equation by moving the existing constant to the right-hand side. To do so, $ac $ will be subtracted from both sides of the equation.
The constant needed to complete the square can now be identified by focusing on the x-term, while ignoring the rest. One way to find this constant is by squaring half the coefficient of the x-term, which in this case is $ab .$
Note that leaving the constant as a power makes the next steps easier to perform.
### 3

The square can now be completed by adding the $constant$ found in Step 2 to both sides of the equation.
### 4

The perfect square trinomial can now be factored and rewritten as the square of a binomial.
The process of completing the square is now finished.
### 5

Finally, the right-hand side of the equation can be simplified.
Now, there is only one x-term. To isolate x, it is necessary to take square roots on both sides of the equation. This results in both a positive and a negative term on the right-hand side.
Now, the equation can be further simplified to isolate x.
Finally, the Quadratic Formula has been obtained.

Factor Out the Coefficient of x2

Identify the Constant Needed to Complete the Square

Complete the Square

$x_{2}+ab x=-ac ⇕Perfect Square Trinomialx_{2}+ab x+(2ab )_{2} =Constant-ac +(2ab )_{2} $

The first three terms form a perfect square trinomial, which can be factored as the square of a binomial. The other two terms do not contain the variable x. Therefore, their value is constant.
Factor the Perfect Square Trinomial

$x_{2}+ab x+(2ab )_{2}=-ac +(2ab )_{2}$

DenomMultFracToNumber

$2⋅2a =a$

$x_{2}+2(2ab )x+(2ab )_{2}=-ac +(2ab )_{2}$

CommutativePropMult

Commutative Property of Multiplication

$x_{2}+2x(2ab )+(2ab )_{2}=-ac +(2ab )_{2}$

FacPosPerfectSquare

a2+2ab+b2=(a+b)2

$(x+2ab )_{2}=-ac +(2ab )_{2}$

Simplify the Equation

$(x+2ab )_{2}=-ac +(2ab )_{2}$

Simplify right-hand side

CommutativePropAdd

Commutative Property of Addition

$(x+2ab )_{2}=(2ab )_{2}−ac $

PowQuot

$(ba )_{m}=b_{m}a_{m} $

$(x+2ab )_{2}=(2a)_{2}b_{2} −ac $

PowProdII

$(ab)_{m}=a_{m}b_{m}$

$(x+2ab )_{2}=4a_{2}b_{2} −ac $

ExpandFrac

$ba =b⋅4aa⋅4a $

$(x+2ab )_{2}=4a_{2}b_{2} −a⋅4ac⋅4a $

CommutativePropMult

Commutative Property of Multiplication

$(x+2ab )_{2}=4a_{2}b_{2} −4a⋅a4ac $

ProdToPowTwoFac

a⋅a=a2

$(x+2ab )_{2}=4a_{2}b_{2} −4a_{2}4ac $

SubFrac

Subtract fractions

$(x+2ab )_{2}=4a_{2}b_{2}−4ac $

$x+2ab =±4a_{2}b_{2}−4ac $

Solve for x

SqrtQuot

$ba =b a $

$x+2ab =±4a_{2} b_{2}−4ac $

SqrtProd

$a⋅b =a ⋅b $

$x+2ab =±2a_{2} b_{2}−4ac $

SqrtPowToNumber

$a_{2} =a$

$x+2ab =±2ab_{2}−4ac $

SubEqn

$LHS−2ab =RHS−2ab $

$x=-2ab ±2ab_{2}−4ac $

MoveNegFracToNum

Put minus sign in numerator

$x=2a-b ±2ab_{2}−4ac $

AddSubFrac

Add and subtract fractions

$x=2a-b±b_{2}−4ac $

Use the quadratic formula to solve the equation.

2x2−4x−16=0

Show Solution

Notice that the given equation is written in standard form. Thus, it can be solved using the quadratic formula. To begin, it's necessary to note the values of a,b, and c. It can be seen that
The solutions to the equation are x=-2 and x=4.

$a=2,b=-4,andc=-16.$

To solve the equation, we can substitute these values into the formula and simplify. Remember, since a quadratic function can have 0,1, or 2 roots, this equation can have 0,1, or 2 real solutions. 2x2−4x−16=0

UseQuadForm

Use the Quadratic Formula: $a=2,b=-4,c=-16$

$x=2⋅2-(-4)±(-4)_{2}−4⋅2(-16) $

NegNeg

-(-a)=a

$x=2⋅24±(-4)_{2}−4⋅2(-16) $

CalcPowProd

Calculate power and product

$x=44±16+128 $

AddTerms

Add terms

$x=44±144 $

CalcRoot

Calculate root

$x=44±12 $

StateSol

State solutions

$x=-8/4x=16/4 $

CalcQuot

Calculate quotient

$x_{1}=-2x_{2}=4 $

In the Quadratic Formula, the expression b2−4ac, which is under the radical symbol, is called the discriminant.

A quadratic equation can have two, one, or no real solutions. Since the discriminant is under the radical symbol, its value determines the number of real solutions of a quadratic equation.

Value of the Discriminant | Number of Real Solutions |
---|---|

b2−4ac>0 | 2 |

b2−4ac=0 | 1 |

b2−4ac<0 | 0 |

Moreover, the discriminant determines the number of x-intercepts of the graph of the related quadratic function.

Determine the number of real solutions to the equations without solving them.

$x_{2}−2x+9=0andx_{2}−4x+4=0$

Show Solution

It's possible to use the discriminant of the quadratic formula to determine the number of solutions a quadratic equation has. We'll first focus on x2−2x+9=0. Since the equation is written in standard form, we can see that a=1,b=-2, and c=9. We can substitute these values into the discriminant and simplify.

b2−4ac

SubstituteValues

Substitute values

(-2)2−4⋅1⋅9

CalcPowProd

Calculate power and product

4−36

SubTerm

Subtract term

-32

b2−4ac

SubstituteValues

Substitute values

(-4)2−4⋅1⋅4

CalcPowProd

Calculate power and product

16−16

SubTerm

Subtract term

0

{{ 'mldesktop-placeholder-grade' | message }} {{ article.displayTitle }}!

{{ focusmode.exercise.exerciseName }}